PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT PADA MATERI MATRIKS DI KELAS XI SMA MUJAHIDIN - Melinda, Melinda; Hamdani, Hamdani; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know the effectiveness of the Cooperative Learning model of the Numbered Head Together (NHT) type in the material Matriks in class XI of SMA Mujahidin Pontianak. As for this research in terms from three aspects, among others: The teacher'sÂ Implementation managing learning, students activities, and completeness of learning students outcomes. The research method used was the experimental method, with a pre-experimental design. The research sample is students in class XI MIPA 3. Based on data analysis that reviewed three aspects, the results were (1) the implementation of learning management was categorized well with an average score of 3.53. (2) The activities of students are classified as active, namely 73,68%. (3) The learning outcomes of students in a classical manner are 27 students or 79,41% who achieve minimal completeness. The conclusion of this research was that Â of the Cooperative Learning model of the Numbered Head Together (NHT) type is effective to be applied to in the material Matriks in class XI SMA Mujahidin Pontianak.Â Keywords: Cooperative learning model, Matriks, NHT type